Molecular breeding for resistance to biotic threats in kiwifruit (Actinidia chinensis) : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, Manawatu, New Zealand - Flay, Casey Damian (Massey University, 2023)
This thesis takes a genomic approach to assist kiwifruit breeding programs by identifying genomic loci that contribute to resistance to biotic threats. Three different biotic threats were investigated that represent some of the most destructive to the kiwifruit industry. These were made up of two pests including latania scale (Hemiberlesia lataniae) and Brown headed leafroller (Ctenopseustis obliquana) and the pathogen Psa (Pseudomonas syringae pv. actinidiae). Together these pests and pathogen represent the predominant feeding mechanisms of, sucking from H. lataniae, chewing from C. obliquana, and infection from the necrotrophic pathogen Psa. The inclusion of these pests and pathogen was thought to provide a well-rounded knowledge of the molecular mechanisms that influence both monogenic and polygenic resistance traits in kiwifruit. Moreover, because these experiments were conducted on multiple kiwifruit families at different sites over time with multiple interactions occurring between organisms, an appreciation was gained for the sources of error that affect experiments, and the effects of those errors on the interpretation of the resulting genomic data. The projects that make up this thesis first analyse kiwifruit (Actinidia chinensis var. chinensis) families of different sizes to identify the molecular architecture for resistance to H. lataniae. Once the monogenic region for resistance to H. lataniae was identified, existing datasets were interrogated for individuals with the loci associated with resistance. Furthermore, due to an absence of H. lataniae resistance in the elite tetraploid gold fleshed A. chinensis var. chinensis breeding program, a diploid individual resistant to H. lataniae that produced unreduced gametes was crossed with tetraploid males and screened for tetraploid individuals that contained markers for H. lataniae resistance. Unfortunately, the experiments investigating the molecular architecture for resistance of A. chinensis var. chinensis to C. obliquana using genotyping by sequencing (GBS) data was unsuccessful due to multiple factors discussed in chapter 4. The last project broke away from the traditional association mapping approach to identify quantitative trait loci (QTL) for Psa resistance from several A. chinensis families that had lost individuals due to Psa. This fast, inexpensive, and powerful approach used a modified bulked segregant analysis (BSA) with bulking methods similar to that of selection mapping. The methodology was validated using pools created with a variable number of males and the sensitivity of detection determined by identifying QTL at the known sex locus. The full experiment then analysed whole genome sequence (WGS) data from eight pools containing multiple families to identify QTL associated with survival to Psa. Together these experiments will advance the kiwifruit breeding program by providing the molecular architecture for two of the most prevalent biotic threats affecting kiwifruit production. Utilising the markers for resistance to H. lataniae and developing markers to target the QTL for resistance to Psa will enable breeding programs to use these markers as selection criteria in commercial breeding programs, increasing the rate at which cultivars resistant to these biotic threats can be developed.
Keywords: molecular plant breeding, kiwifruit; 310805 Plant pathology